PENGARUH MODEL PEMBELAJARAN CONCEPT ATTAINMENT TERHADAP KEMAMPUAN GENERALISASI MATEMATIS DAN KEMAMPUAN BERPIKIR GEOMETRI VAN HIELE - Desfa Lusiana; Zamzaili Zamzaili; Hari Sumardi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study intended to know the effect of the Concept Attainment Model on the students in the mathematical generalization ability and Van Hiele's geometry thinking ability. This study used a quasi-experimental method. The population included all students of SMPN 16, Bengkulu, in the academic year 2020/2021. The sample consisted of two classes selected using purposive sampling techniques. Mathematical generalization ability and Van Hiele's geometry thinking ability were measured by a test that has been valid and reliable. Furthermore, the data obtained were analyzed using the test MANCOVA with a 5% significant level (α = 0.05). The result of the hypothesis test indicated that there was a positive effect of the Concept Attainment Model on mathematical generalization ability and Van Hiele's geometry thinking ability